ISOLATION OF AN INTERMEDIATE IN CLAVULANIC ACID BIOSYNTHESIS - Baldwin, J; Adlington, R; Bryans, J; Bringhen, A; Coates, J; Crouch, N; Lloyd, M; Schofield, C; Elson, S; Baggaley, K; Cassells, R; Nicholson, N (1990)
The operation of a primary isotope effect was utilised to enable a hitherto unknown intermediate in clavulanic acid biosynthesis to be isolated and characterised.